Proteolysis of BB0323 results in two polypeptides that impact physiologic and infectious phenotypes in Borrelia burgdorferi. Issue 3 (26th March 2013) - Kariu, Toru; Yang, Xiuli; Marks, Carolyn B.; Zhang, Xinyue; Pal, Utpal
Summary: Borrelia burgdorferi gene product BB0323 is required for cell fission and pathogen persistence in vivo . Here, we show that BB0323, which is conserved among globally prevalent infectious strains, supports normal spirochaete growth and morphology even at early phases of cell division. We demonstrate that native BB0323 undergoes proteolytic processing at the C‐terminus, at a site after the first 202 N‐terminal amino acids. We further identified a periplasmic BB0323 binding protein in B. burgdorferi, annotated as BB0104, having serine protease activity responsible for the primary cleavage of BB0323 to produce discrete N‐ and C‐terminal polypeptides. These two BB0323 polypeptides interact with each other, and either individually or as a complex, are associated with multiple functions in spirochaete biology and infectivity. While N‐terminal BB0323 is adequate to support cell fission, the C‐terminal LysM domain is dispensable for this process, despite its ability to bind B. burgdorferi peptidoglycan. However, the LysM domain or the precisely processed BB0323 product is essential for mammalian infection. As BB0323 is a membrane protein crucial for B. burgdorferi survival in vivo, exploring its function may suggest novel ways to interrupt infection while enhancing our understanding of the intricate spirochaete fission process.